2018
DOI: 10.1002/jls.21569
|View full text |Cite
|
Sign up to set email alerts
|

Nature‐Based Training Program Fosters Authentic Leadership

Abstract: Authentic leadership is frequently promoted as a leadership style that responds to the contemporary challenges that leaders face. The current experimental study (n = 66) tested intrapersonal change toward authentic leadership after participation in a nature‐based training program that included a stay in remote wilderness without any facilities. Authentic leadership was measured before, immediately after, and 1 year after the training program. All components of authentic leadership increased, namely self‐awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The tool was developed by Droffelaar and Jacobs (2018); Sercan, (2016) which was adopted and modified by the researchers. The tool consisted of two parts as follows:…”
Section: Tool (2): Authentic Leadership Perception Questionnairementioning
confidence: 99%
“…The tool was developed by Droffelaar and Jacobs (2018); Sercan, (2016) which was adopted and modified by the researchers. The tool consisted of two parts as follows:…”
Section: Tool (2): Authentic Leadership Perception Questionnairementioning
confidence: 99%
“…Secondly, some mentioned the development of managers' authentic leadership as a potential mediator in the burnout prevention of employees. Considering the feasibility in the organization and acknowledging the positive role of NC in developing authentic leadership ( 72 ), an open program NBT for leaders of different participating organizations will be offered. The open program, consisting of nature-based leadership-related and NC exercises, will promote processes such as shared learning, crosspollination and mutual support between the leaders of the participating organizations.…”
Section: Resultsmentioning
confidence: 99%
“…0.7) following the wilderness-based training program to such extent that further research was merited. The findings demonstrated that the training program leads to changes in leadership style lasting at least a year (Van Droffelaar and Jacobs, 2018).…”
Section: Authentic Leadership and Wildernessmentioning
confidence: 91%